The Relationship between Fast Food, Sleep Patterns, and Facial Hygiene with the Severity of Acne Vulgaris - Winawati Eka Putri; Naila Farah Hilda; Fiona Restu Kusumah; Ardhien Alif Yulian; Maria Ulfa; Meidyta Sinantryana Widyaswari; Niken Adiba Nadya (Biomolecular and Health Science Journal)
Introduction: Acne vulgaris (AV) is a chronic inflammatory disease that affects several parts of the body, such as hair follicles, the face, and the neck. AV often occurs in adolescents due to increased sebum production, hyperkeratinization of pilosebaceous follicles, and inflammation. AV is a multifactorial inflammation that can be triggered by several factors, such as frequent fast-food consumption, poor facial hygiene, and poor sleep habit. This research was performed to examine the relationship between fast-food consumption, facial hygiene, and sleep patterns with AV severity among students of Universitas Nahdlatul Ulama Surabaya (UNUSA). Methods: An analytic observational with a cross-sectional approach was conducted on 60 respondents. The data were collected using the Dermatology Life Quality Index, based on which respondents’ quality of life related to skin problems was examined. Meanwhile, the Food Frequency Questionnaire was distributed to assess food consumption, and a questionnaire measuring facial hygiene was used to assess respondents’ face condition. Furthermore, respondents’ quality of sleep was measured using the Pittsburgh Sleep Quality Index. The aforementioned data then underwent univariate and bivariate analysis. Results: The results showed that the most consumed types of fast food by UNUSA students were fried chicken, and while the severity of AV was considered low. Most of the students have poor sleep quality. A significant association was found between the frequency of fast-food consumption, facial hygiene (P = 0.041), and sleep patterns (P = 0.043) with the severity of AV. Conclusions: The frequency of fast-food consumption, facial hygiene, and sleep patterns are significantly associated with the severity of AV among UNUSA students.